Student-teachers’ identity construction and its connection with student-centered approaches : a narrative study [E-Book] - Ramos Holguín, Bertha; Aguirre Morales, Jahir; Torres Cepeda, Nancy María (Editorial UPTC, 2021)
Eng: This book shows the paths student-teachers embark on the construction of their identies within the frame of a student-centered approach perspective. Understanding teacher identity construction suggests perceiving a broad and socially-driven dimension. In such a way , humansare contextual, political, and culturally situated to continually make sense of their"selves" on a daily-basis. Delving into teacher identity construction issues is a relevant constituent for the contininual professional development of English language teachers.